Multiple Solid Organ Transplantation in Telomeropathy: Case Series and Literature Review. Issue 10 (October 2018) - Lebeer, Marnix; Wuyts, Wim A.; Cassiman, David; Laleman, Wim; Nevens, Frederik; Pirenne, Jacques; Monbaliu, Diethard; Roskams, Tania; Verbeken, Eric K.; Neyrinck, Arne P.; Van Raemdonck, Dirk E.; Verleden, Geert M.; et al.
Abstract : Background: Solid organ transplantation is a valid treatment option for selected patients with organ failure due to an underlying telomeropathy; however, the feasibility of multiple-organ transplantation if several organs are compromised is unclear. Methods: We describe 2 patients with telomeropathy due to heterozygous telomerase RNA component or telomerase reverse transcriptase mutation, who successfully underwent serial or combined liver and lung transplantation for concurrent liver fibrosis/cirrhosis and pulmonary fibrosis. Results: Despite a challenging posttransplant course, long-term outcomes were favorable, with both patients doing fine now, respectively, 12/20 and 24 months after multiple-organ transplantation. Conclusions: To our knowledge, this is the first report of multiple solid organ transplantation in documented telomeropathy. These cases highlight current difficulties of timely diagnosis, therapeutic approach, and postoperative complications in telomeropathy patients in whom several organs are affected. Abstract : Telomerase RNA component (TERC) is the template that telomerase reverse transcriptase (TERT) uses to add telomere-repeats to DNA. The authors describe successful lung-liver transplants in two patients with liver fibrosis/cirrhosis and pulmonary fibrosis from telomeropathies from heterozygous mutations in TERC or TERT.